Gambaran Karakteristik, Pengetahuan, Dan Sikap Petani Pengguna Pestisida Di Kecamatan Pasirian Kabupaten Lumajang - Fitri Dika Maharani; Erma Sulistyaningsih; Hadi Prayitno (Multidisciplinary Journal, 2020)
Improper use of pesticides can cause serious short-term or long-term health problems. The process of pesticides into the body is through the skin, respiration, mouth, and mucous membranes. The use of personal protective equipment (PPE) is an effort to maintain the safety and health of farmers in using pesticides. This study aims to describe the characteristics, knowledge, attitudes and relationships with the use of PPE in Pasirian District, Lumajang Regency. This type of research is a descriptive analysis using a cross-sectional quantitative approach. The sample size used was 100 farmers who were selected with predetermined criteria. Collecting data using a questionnaire. Data analysis used univariate with frequency distribution and bivariate with Spearman rank test. The results showed that most of the farmers (39%) aged 32-43 years, 39% had no primary school education, and 47% had experience as farmers for 5 years. Most of the farmers (50%) have good knowledge about pesticides and 62% have sufficient attitudes regarding the use of pesticides. Knowledge and attitudes related to the use of PPE with low and moderate levels of correlation. Key words: attitude, farmers, knowledge, pesticides